2016
DOI: 10.3390/ijms17122096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the CRAC Peptide, VLNYYVW, on mPTP Opening in Rat Brain and Liver Mitochondria

Abstract: The translocator protein (TSPO; 18 kDa) is a high-affinity cholesterol-binding protein located in the outer membrane of mitochondria. A domain in the C-terminus of TSPO was characterized as the cholesterol recognition/interaction amino acid consensus (CRAC). The ability of the CRAC domain to bind to cholesterol led us to hypothesize that this peptide may participate in the regulation of mitochondrial membrane permeability. Herein, we report the effect of the synthetic CRAC peptide, VLNYYVW, on mitochondrial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Moreover, the effect of ligands may also depend on their concentration. Thus, we previously showed that different concentrations of PK11195 can have opposite effects on the mPTP [35,74], which is apparently associated with different mechanisms of action. The ligands in the nanomolar concentration range studied in this work are likely to have a greater specificity for the TSPO, while higher concentrations can lead to other, TSPO-independent effects of both PPIX and PK11195.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the effect of ligands may also depend on their concentration. Thus, we previously showed that different concentrations of PK11195 can have opposite effects on the mPTP [35,74], which is apparently associated with different mechanisms of action. The ligands in the nanomolar concentration range studied in this work are likely to have a greater specificity for the TSPO, while higher concentrations can lead to other, TSPO-independent effects of both PPIX and PK11195.…”
Section: Discussionmentioning
confidence: 96%
“…It was previously shown that peptide VLNYYVW, a fragment of a CRAC motif without a cationic amino acid, cholesterol-dependently modulates the activity of cultured macrophages IC-21 [29][30][31]. According to Azarashvili et al [48], the same peptide prevents the opening of non-selective mitochondrial pores (mPTP) and the release of cytochrome c, as well as other apoptotic factors in mitochondria isolated from rat brain.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 Moreover, its structure was composed of an integral membrane protein built by the five transmembrane alpha-helices, namely two intramitochondrial loops, two extramitochondrial loops, one extramitochondrial C-terminal, one intramitochondrial N-terminal, and one cholesterol-binding domain. 50 Previous studies reported the occurrence of TSPO as a monomer, but current investigations suggested that it could generate oligomeric aggregates with itself and other proteins. There was an indication that it could transform into homo-oligomers to provide a binding site for cholesterol.…”
Section: Clinical Implications Of Tspomentioning
confidence: 88%